The Use of BIM Technology in Analyzing Building Energy and Economic Feasibility of Solar Panel - Rifqi, Muhammadiya; Fitriani, Heni; Wardhani, Puteri Kusuma (Indonesian Journal of Environmental Management and Sustainability, 2021)
Buildings contribute more than 40% of world energy consumption, so it is feared that it will cause energy problems in the future, especially in the construction sector. One solution to reducing this problem is by analyzing energy use at the initial design stage and utilizing solar energy as one of the solar power plants (PLTS) in office buildings. To analyze the use of energy in buildings, Building Information Modeling (BIM) was used. The purpose of this research is to analyze the annual energy level of office buildings in Palembang using BIM software, namely Autodesk Revit. The number of solar panels as well as the amount of energy were also identified using web-based software (HelioScope) resulting the economic feasibility as indicated by the installation of solar panels as a component of PV mini-grid. The results showed that the use of BIM technology in analyzing building energy can provide a detailed description of the building model at the design stage. Revit analysis indicates that the building consumed electrical energy per year for about 3,647,713 kWh with a roof area of 1,657 m2. In addition, based on the HelioScope analysis, the use of renewable energy from the installation of PLTS was 152,900 kWh/year. Meanwhile, for economic feasibility analysis, the installation of PLTS in office buildings can provide a positive Net Present Value (NPV), indicating a feasible project.